A paradox of the ovulatory patterns in the living laboratory, African giant pouched rat (Cricetomys gambianus) from Tanzania - Ngalameno, Mungo (Journal of Ideas in Health, 2024)
The African giant pouched rat (Cricetomys gambianus) has emerged as a valuable model animal deployed in biomedical and other researches with humanitarian application due to its intelligence, socio-behavior, and adaptability to captivity. This rodent lives in solitary and belongs to the family Cricetidae that synchronises sexual behavioral onset with subsequent maturation of their gonads and gametes just prior to the beginning of the short rains of Tanzania. The current study set out to investigate whether ovulation in this species is induced or spontaneous. The study involved five sexually mature intact tame females and five sexually matured vasectomized wild males. Females were monitored non-invasively for ovarian cyclicity by measuring urinary progesterone every 2 days over 84days. Females were subjected to three separate step-wise experiments with different treatments as follows: step one was singly housed, which served as the control (C), followed by Non-Physical Contact with a vasectomized male (NPC) and Physical Contact with the same vasectomized male (PC), respectively. The average urinary progesterone concentration was similar in all three treatments, with a urinary progesterone spike indicating ovulation occurring in all treatments, suggesting a spontaneous ovulating strategy. However, upon assessment of the male penis, it was revealed that part of the glans penis had small epidermal spines which somehow resembles to those reported in induced ovulators. The findings from this study on the African giant pouched rat leaves a paradox as profiles of progesterone from females strongly suggest a spontaneous pattern of ovulation although the penile morphology of males have features suggesting induced pattern of ovulation.